Method for improving obdurability of Ti-13Nb-13Zr medical titanium alloy manufactured through laser additive

By using spherical Ti-13Nb-13Zr titanium alloy powder in laser additive manufacturing and performing solid solution and aging heat treatment, the problems of low elongation and poor strength and toughness of Ti-13Nb-13Zr medical titanium alloy implant materials for laser additive manufacturing are solved, and the strength and plastic toughness are achieved well matched, meeting the application requirements of clinical implants.

CN119681280APending Publication Date: 2025-03-25KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411955617.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Laser additive manufacturing Ti-13Nb-13Zr medical titanium alloy implant materials have problems of low elongation and poor strength and toughness, which are difficult to meet the application requirements of clinical implants.

Method used

The spherical Ti-13Nb-13Zr titanium alloy powder with a particle size of 15 to 45 μm was used for laser additive manufacturing. After vacuum drying, laser additive manufacturing, solid solution and aging heat treatment, Ti-13Nb-13Zr titanium alloy was formed in solid solution and aging state.

Benefits of technology

The strength, elongation and strength and toughness of Ti-13Nb-13Zr medical titanium alloy have been significantly improved, and the mechanical performance index is better than the national standard requirements of traditional Ti-6Al-4V titanium alloy implants, and can meet the requirements of clinical medical implant materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a method for improving the obdurability of a Ti-13Nb-13Zr medical titanium alloy manufactured through laser additive manufacturing. The method is characterized by comprising the following steps that (1) spherical Ti-13Nb-13Zr titanium alloy powder serves as a raw material; (2) heating to 70-80 DEG C under vacuum, and keeping the temperature for 30-60 minutes; (3) in a vacuum and argon atmosphere, under the conditions that the laser power is 90-120 W, the scanning speed is 1300-1500 mm / min, the scanning distance is 0.03-0.07 mm and the layer height is 0.02-0.05 mm, powder is continuously laid and melted according to preset layer cutting data and layer cutting scanning data; (4) heating to 640-660 DEG C at the rate of 3-10 DEG C / min in a vacuum and argon atmosphere, preserving heat for 50-80 minutes, quenching in water, and cooling to the room temperature, and (5) heating to 510-530 DEG C at the rate of 3-10 DEG C / min in a vacuum and argon atmosphere, preserving heat for 5-6 hours, and air-cooling to the room temperature, thereby obtaining the aged Ti-13Nb-13Zr titanium alloy. The tensile strength, yield strength and ductility of the Ti-13Nb-13Zr medical titanium alloy manufactured by the laser additive are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the strength and toughness of Ti-13Nb-13Zr medical titanium alloy manufactured by laser additive manufacturing, and belongs to the technical field of titanium alloy additive manufacturing. Background Art

[0002] Ti-13Nb-13Zr titanium alloy is a near-β-type titanium alloy with the advantages of good toughness, low elastic modulus, good wear and corrosion resistance, fatigue resistance and good biocompatibility, and does not contain toxic elements. It has obvious application prospects in artificial substitutes or implants for hard tissues. The shapes of implant materials currently used in clinical applications are relatively complex, and additive manufacturing technology represented by selective laser melting (SLM) technology can melt and solidify metal powder layer by layer through laser to obtain the required geometric shape. It has many advantages such as high material utilization and direct production based on a geometric constraint-free mode, especially in the field of personalized customized implants.

[0003] However, during the laser additive manufacturing process, the rapid melting and cooling of the alloy spherical powder not only leaves residual stress between the various cladding layers, but also makes the alloy structure easily form columnar crystals along the printing direction, resulting in poor mechanical properties of the prepared alloy. Subsequent heat treatment is required to eliminate residual stress, adjust the alloy's organizational morphology, and improve mechanical properties. Relevant studies have shown that although the mechanical properties of Ti-13Nb-13Zr titanium alloy prepared by laser additive manufacturing technology can be improved through heat treatment (such as annealing), there is still a mismatch between strength and plasticity, which makes it difficult to meet the application requirements of clinical implants. Summary of the invention

[0004] In order to overcome the shortcomings of the existing technology, especially the low elongation and poor toughness of the existing laser additively manufactured Ti-13Nb-13Zr medical titanium alloy implant materials, the present invention provides a method for improving the strength and toughness of laser additively manufactured Ti-13Nb-13Zr medical titanium alloy.

[0005] The present invention is accomplished by the following technical scheme: a method for improving the strength and toughness of Ti-13Nb-13Zr medical titanium alloy manufactured by laser additive manufacturing, characterized by comprising the following steps:

[0006] (1) Using spherical Ti-13Nb-13Zr titanium alloy powder with a particle size of 15 to 45 μm as raw material;

[0007] (2) placing the spherical Ti-13Nb-13Zr titanium alloy powder of step (1) in a vacuum drying oven, heating to 70-80° C. for drying under a vacuum degree of 10-25 Pa, and keeping the temperature for 30-60 min to obtain a dried powder;

[0008] (3) placing the spherical Ti-13Nb-13Zr titanium alloy powder dried in step (2) into a powder box of a laser additive manufacturing device, evacuating the powder to 8-10 Pa, and continuously introducing argon gas with a purity of 99.99%. Under the process conditions of laser power of 90-120 W, scanning speed of 1300-1500 mm / min, scanning spacing of 0.03-0.07 mm, and layer height of 0.02-0.05 mm, the powder spreading-melting is continuously performed according to the pre-set layer cutting data and layer cutting scanning data of the laser additive manufacturing device until a deposited Ti-13Nb-13Zr titanium alloy is obtained;

[0009] (4) placing the deposited Ti-13Nb-13Zr titanium alloy obtained in step (3) into a vacuum tube furnace, evacuating to 20-25 Pa, and then continuously introducing argon gas with a purity of 99.99%; heating to 640-660° C. at a rate of 3-10° C. / min, keeping the temperature for 50-80 min, then taking out, quenching in water and cooling to room temperature to obtain a solid solution Ti-13Nb-13Zr titanium alloy;

[0010] (5) The solid solution Ti-13Nb-13Zr titanium alloy obtained in step (4) is placed in a vacuum tube furnace, evacuated to 20-25 Pa, and then continuously introduced with argon gas with a purity of 99.99%; the temperature is raised to 510-530°C at a rate of 3-10°C / min, kept at this temperature for 5-6 hours, then taken out and air-cooled to room temperature to obtain an aged Ti-13Nb-13Zr titanium alloy.

[0011] The slice data and slice scanning data preset by the laser additive manufacturing device in step (3) are obtained by the following conventional method: drawing a three-dimensional model, slicing the drawn three-dimensional model in layers along the height direction, scanning the inside of each slice, and importing the obtained slice data and slice scanning data into the laser additive manufacturing device.

[0012] Preferably, the chemical composition of the spherical Ti-13Nb-13Zr titanium alloy powder in the step (1) is as follows: Nb: 12.5~14.0wt.%, Zr: 12.5~14.0wt.%, Fe: ≤0.25wt.%, C: ≤0.08wt.%, N: ≤0.05wt.%, H: ≤0.012wt.%, O: ≤0.15wt.%, and the remainder is Ti.

[0013] Preferably, the spherical Ti-13Nb-13Zr titanium alloy powder in step (1) is prepared by electrode induction melting and inert gas atomization.

[0014] The present invention has the following advantages and beneficial effects:

[0015] Through the above technical scheme, the present invention not only significantly improves the strength, elongation and toughness combination of laser additively manufactured Ti-13Nb-13Zr medical titanium alloy, but also the mechanical performance indicators are better than the national standard requirements of traditional Ti-6Al-4V titanium alloy implants. The pre-alloyed spherical Ti-13Nb-13Zr powder prepared by electrode induction melting and inert gas atomization is used as the raw material. It has the advantages of high sphericity, good fluidity, high purity and low gas impurity content, and can achieve precise control of elements and effectively avoid the segregation problem of chemical composition. The present invention regulates the organizational morphology of laser additively manufactured Ti-13Nb-13Zr medical titanium alloy through solid solution + aging strengthening heat treatment, fully releases the residual stress, decomposes the metastable phase and precipitates a stable and fine α phase, thereby improving the mechanical properties of the alloy, and the tensile strength R m ≥970MPa, yield strength R p0.2 The room temperature tensile mechanical properties are better than those of Ti-6Al-4V in GB / T 13810-2017 (R m ≥930MPa, R p0.2 ≥860MPa, A≥10%), which can meet the requirements of clinical medical implant materials and has good prospects for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a morphology diagram of the Ti-13Nb-13Zr titanium alloy spherical powder raw material according to an embodiment of the present invention.

[0017] Figure 2 This is a microstructure morphology diagram of the deposited Ti-13Nb-13Zr titanium alloy prepared in an embodiment of the present invention.

[0018] Figure 3 This is the microstructure of the solution-aged Ti-13Nb-13Zr titanium alloy prepared in an embodiment of the present invention.

[0019] Figure 4 It is a tensile mechanical property curve diagram of the Ti-13Nb-13Zr titanium alloy prepared in Examples 1-4 of the present invention after heat treatment. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with specific implementation methods, but the protection scope of the present invention is not limited to the above contents.

[0021] The chemical composition of the spherical Ti-13Nb-13Zr titanium alloy powder used in the embodiment of the present invention is as follows: Nb: 13.0782wt.%, Zr: 13.5846wt.%, Fe: 0.0419wt.%, C: 0.0099wt.%, N: 0.0127wt.%, H: 0.0015wt.%, O: 0.1304wt.%, and the balance is Ti;

[0022] The spherical Ti-13Nb-13Zr titanium alloy powder used in the embodiment of the present invention is prepared by a conventional electrode induction melting inert gas atomization method.

[0023] Example 1

[0024] A method for improving the toughness of laser additively manufactured Ti-13Nb-13Zr medical titanium alloy, comprising the following steps:

[0025] (1) Using spherical Ti-13Nb-13Zr titanium alloy powder with a particle size of 15 to 45 μm as raw material;

[0026] (2) placing the spherical Ti-13Nb-13Zr titanium alloy powder of step (1) in a vacuum drying oven, heating to 70° C. for drying under a vacuum degree of 20 Pa, and keeping the temperature for 30 min to obtain a dried powder;

[0027] (3) placing the spherical Ti-13Nb-13Zr titanium alloy powder dried in step (2) into a powder box of a laser additive manufacturing device, evacuating the powder to 8 Pa, and continuously introducing argon gas with a purity of 99.99%. Under the process conditions of laser power of 100 W, scanning speed of 1400 mm / min, scanning spacing of 0.06 mm, and layer height of 0.03 mm, the powder spreading-melting is continuously performed according to the pre-set layer cutting data and layer cutting scanning data of the laser additive manufacturing device until a deposited Ti-13Nb-13Zr titanium alloy is obtained;

[0028] The slice data and slice scanning data preset by the laser additive manufacturing device are obtained by the following conventional method: drawing a three-dimensional model, slicing the drawn three-dimensional model in layers along the height direction, scanning the inside of each slice, and importing the obtained slice data and slice scanning data into the laser additive manufacturing device;

[0029] (4) placing the deposited Ti-13Nb-13Zr titanium alloy obtained in step (3) into a vacuum tube furnace, evacuating to 20 Pa, and then continuously introducing argon gas with a purity of 99.99%; heating to 660° C. at a rate of 5° C. / min, and keeping the temperature for 60 min. After the insulation is completed, taking out the sample, quenching it in water and cooling it to room temperature to obtain a solid solution Ti-13Nb-13Zr titanium alloy;

[0030] (5) The solid solution Ti-13Nb-13Zr titanium alloy obtained in step (4) is placed in a vacuum tube furnace, evacuated to 20 Pa, and then continuously introduced with argon gas having a purity of 99.99%; the temperature is raised to 510°C at a rate of 5°C / min, and the mixture is kept warm for 5.5 h. After the heat preservation is completed, the sample is taken out and air-cooled to room temperature to obtain an aged Ti-13Nb-13Zr titanium alloy having the following chemical composition.

[0031] The heat-treated aged Ti-13Nb-13Zr titanium alloy obtained in this embodiment was subjected to a mechanical tensile test at room temperature according to GB / T228.1-2021 standard, and the results are shown in Table 1. The test results show that the obtained Ti-13Nb-13Zr titanium alloy has excellent toughness and an average tensile strength R m The average yield strength R is 1034MPa. p0.2 The room temperature tensile mechanical properties are better than those of Ti-6Al-4V in GB / T 13810-2017 (R m ≥930MPa, R p0.2 ≥860MPa, A≥10%), achieving a good match between strength and plasticity, thus having excellent load-bearing capacity and anti-deformation ability, which is conducive to long-term effective implantation.

[0032] Table 1 Tensile properties of Ti-13Nb-13Zr titanium alloy of Example 1

[0033] Sample <![CDATA[R m / MPa]]> <![CDATA[R p0.2 / MPa]]> A / % 1 1027 956 11.5 2 1009 921 10.5 3 1065 983 11.9 average value 1034 953 11.3

[0034] Example 2

[0035] A method for improving the toughness of laser additively manufactured Ti-13Nb-13Zr medical titanium alloy, comprising the following steps:

[0036] (1) Using spherical Ti-13Nb-13Zr titanium alloy powder with a particle size of 15 to 45 μm as raw material;

[0037] (2) placing the spherical Ti-13Nb-13Zr titanium alloy powder of step (1) in a vacuum drying oven, heating to 70° C. for drying under a vacuum degree of 20 Pa, and keeping the temperature for 30 min to obtain a dried powder;

[0038] (3) The spherical Ti-13Nb-13Zr titanium alloy powder dried in step (2) is placed in a powder box of a laser additive manufacturing device, evacuated to 8 Pa, and then continuously introduced with argon gas having a purity of 99.99%. Under the process conditions of laser power 110 W, scanning speed 1500 mm / min, scanning spacing 0.06 mm, and layer height 0.03 mm, the powder spreading-melting is continuously performed according to the pre-set layer cutting data and layer cutting scanning data of the laser additive manufacturing device until a deposited Ti-13Nb-13Zr titanium alloy is obtained;

[0039] The slice data and slice scanning data preset by the laser additive manufacturing device are obtained by the following conventional method: drawing a three-dimensional model, slicing the drawn three-dimensional model in layers along the height direction, scanning the inside of each slice, and importing the obtained slice data and slice scanning data into the laser additive manufacturing device;

[0040] (4) placing the deposited Ti-13Nb-13Zr titanium alloy obtained in step (3) into a vacuum tube furnace, evacuating to 20 Pa, and then continuously introducing argon gas with a purity of 99.99%; heating to 640° C. at a rate of 5° C. / min, and keeping the temperature for 70 min. After the insulation is completed, taking out the sample, quenching it in water and cooling it to room temperature to obtain a solid solution Ti-13Nb-13Zr titanium alloy;

[0041] (5) The solid solution Ti-13Nb-13Zr titanium alloy obtained in step (4) is placed in a vacuum tube furnace, evacuated to 20 Pa, and then continuously introduced with argon gas having a purity of 99.99%; the temperature is raised to 510°C at a rate of 5°C / min, and the mixture is kept warm for 5.5 h. After the heat preservation is completed, the sample is taken out and air-cooled to room temperature to obtain an aged Ti-13Nb-13Zr titanium alloy having the following chemical composition.

[0042] The heat-treated aged Ti-13Nb-13Zr titanium alloy obtained in this embodiment was subjected to a tensile mechanical test at room temperature according to GB / T228.1-2021 standard, and the results are shown in Table 2. The test results show that the obtained Ti-13Nb-13Zr titanium alloy has excellent toughness and an average tensile strength R m The average yield strength is 997MPa. p0.2 The average elongation A is 929MPa and 11.8%, and the room temperature tensile mechanical properties are better than those of the Ti-6Al-4V standard (R m ≥930MPa, R p0.2 ≥860MPa, A≥10%), achieving a good match between strength and plasticity, thus having excellent load-bearing capacity and anti-deformation ability, which is conducive to long-term effective implantation.

[0043] Table 2 Tensile properties of Ti-13Nb-13Zr titanium alloy of Example 2

[0044]

[0045]

[0046] Example 3

[0047] A method for improving the toughness of laser additively manufactured Ti-13Nb-13Zr medical titanium alloy, comprising the following steps:

[0048] (1) Using spherical Ti-13Nb-13Zr titanium alloy powder with a particle size of 15 to 45 μm as raw material;

[0049] (2) placing the spherical Ti-13Nb-13Zr titanium alloy powder of step (1) in a vacuum drying oven, heating to 70° C. for drying under a vacuum degree of 20 Pa, and keeping the temperature for 30 min to obtain a dried powder;

[0050] (3) placing the spherical Ti-13Nb-13Zr titanium alloy powder dried in step (2) into a powder box of a laser additive manufacturing device, evacuating the powder to 8 Pa, and continuously introducing argon gas with a purity of 99.99%. Under the process conditions of laser power of 100 W, scanning speed of 1400 mm / min, scanning spacing of 0.06 mm, and layer height of 0.03 mm, the powder spreading-melting is continuously performed according to the pre-set layer cutting data and layer cutting scanning data of the laser additive manufacturing device until a deposited Ti-13Nb-13Zr titanium alloy is obtained;

[0051] The slice data and slice scanning data preset by the laser additive manufacturing device are obtained by the following conventional method: drawing a three-dimensional model, slicing the drawn three-dimensional model in layers along the height direction, scanning the inside of each slice, and importing the obtained slice data and slice scanning data into the laser additive manufacturing device;

[0052] (4) placing the deposited Ti-13Nb-13Zr titanium alloy obtained in step (3) into a vacuum tube furnace, evacuating to 20 Pa, and then continuously introducing argon gas with a purity of 99.99%; heating to 660° C. at a rate of 5° C. / min, and keeping the temperature for 60 min. After the insulation is completed, taking out the sample, quenching it in water and cooling it to room temperature to obtain a solid solution Ti-13Nb-13Zr titanium alloy;

[0053] (5) The solid solution Ti-13Nb-13Zr titanium alloy obtained in step (4) is placed in a vacuum tube furnace, evacuated to 20 Pa, and then continuously introduced with argon gas with a purity of 99.99%; the temperature is raised to 530°C at a rate of 5°C / min and kept warm for 5 hours. After the insulation is completed, the sample is taken out and air-cooled to room temperature to obtain an aged Ti-13Nb-13Zr titanium alloy with the following chemical composition.

[0054] The heat-treated aged Ti-13Nb-13Zr titanium alloy obtained in this embodiment was subjected to a mechanical tensile test at room temperature according to GB / T228.1-2021 standard, and the results are shown in Table 3. The test results show that the obtained Ti-13Nb-13Zr titanium alloy has excellent toughness and an average tensile strength R m The average yield strength R is 1005MPa. p0.2 The average elongation A is 939MPa and 13.5%, and the room temperature tensile mechanical properties are better than those of the Ti-6Al-4V standard (R m ≥930MPa, R p0.2 ≥860MPa, A≥10%), achieving a good match between strength and plasticity, thus having excellent load-bearing capacity and anti-deformation ability, which is conducive to long-term effective implantation.

[0055] Table 3 Tensile properties of Ti-13Nb-13Zr titanium alloy of Example 3

[0056] Sample <![CDATA[R m / MPa]]> <![CDATA[R p0.2 / MPa]]> A / % 1 1004 943 13.4 2 1013 937 12.9 3 999 938 14.3 average value 1005 939 13.5

[0057] Example 4

[0058] A method for improving the toughness of laser additively manufactured Ti-13Nb-13Zr medical titanium alloy, comprising the following steps:

[0059] (1) Using spherical Ti-13Nb-13Zr titanium alloy powder with a particle size of 15 to 45 μm as raw material;

[0060] (2) placing the spherical Ti-13Nb-13Zr titanium alloy powder of step (1) in a vacuum drying oven, heating to 70° C. for drying under a vacuum degree of 20 Pa, and keeping the temperature for 30 min to obtain a dried powder;

[0061] (3) The spherical Ti-13Nb-13Zr titanium alloy powder dried in step (2) is placed in a powder box of a laser additive manufacturing device, evacuated to 8 Pa, and then continuously introduced with argon gas having a purity of 99.99%. Under the process conditions of laser power 110 W, scanning speed 1500 mm / min, scanning spacing 0.06 mm, and layer height 0.03 mm, the powder spreading-melting is continuously performed according to the pre-set layer cutting data and layer cutting scanning data of the laser additive manufacturing device until a deposited Ti-13Nb-13Zr titanium alloy is obtained;

[0062] The slice data and slice scanning data preset by the laser additive manufacturing device are obtained by the following conventional method: drawing a three-dimensional model, slicing the drawn three-dimensional model in layers along the height direction, scanning the inside of each slice, and importing the obtained slice data and slice scanning data into the laser additive manufacturing device;

[0063] (4) placing the deposited Ti-13Nb-13Zr titanium alloy obtained in step (3) into a vacuum tube furnace, evacuating to 20 Pa, and then continuously introducing argon gas with a purity of 99.99%; heating to 640° C. at a rate of 5° C. / min, and keeping the temperature for 70 min. After the insulation is completed, taking out the sample, quenching it in water and cooling it to room temperature to obtain a solid solution Ti-13Nb-13Zr titanium alloy;

[0064] (5) The solid solution Ti-13Nb-13Zr titanium alloy obtained in step (4) is placed in a vacuum tube furnace, evacuated to 20 Pa, and then continuously introduced with argon gas with a purity of 99.99%; the temperature is raised to 530°C at a rate of 5°C / min and kept warm for 5 hours. After the insulation is completed, the sample is taken out and air-cooled to room temperature to obtain an aged Ti-13Nb-13Zr titanium alloy with the following chemical composition.

[0065] The heat-treated aged Ti-13Nb-13Zr titanium alloy obtained in this embodiment was subjected to a mechanical tensile test at room temperature according to GB / T228.1-2021 standard, and the results are shown in Table 4. The test results show that the obtained Ti-13Nb-13Zr titanium alloy has excellent toughness and an average tensile strength R m The average yield strength R is 984MPa. p0.2 The average elongation A is 901MPa and 13.8%, and the room temperature tensile mechanical properties are better than those of the Ti-6Al-4V standard (R m ≥930MPa, R p0.2 ≥860MPa, A≥10%), achieving a good match between strength and plasticity, thus having excellent load-bearing capacity and anti-deformation ability, which is conducive to long-term effective implantation.

[0066] Table 4 Tensile properties of Ti-13Nb-13Zr titanium alloy of Example 4

[0067] Sample <![CDATA[R m / MPa]]> <![CDATA[R p0.2 / MPa]]> A / % 1 973 874 13 2 971 914 14.4 3 1009 916 14 average value 984 901 13.8

[0068] Figure 2 , 3 The microstructure morphologies of the Ti-13Nb-13Zr titanium alloy prepared in Example 1 in the deposited state and the solution-aged state respectively. It can be seen that the microstructure of the Ti-13Nb-13Zr titanium alloy in the deposited state is β columnar crystals growing in the printing direction, with fine lamellar martensite phase inside. After the solution-aging heat treatment, the martensite phase decomposes and the alloy microstructure is transformed into a basketweave structure, which is composed of alternating needle-shaped secondary α phase and β phase.

[0069] The mechanical properties of the alloys obtained in Examples 1, 2, 3 and 4 are shown in Tables 1, 2, 3, 4 and Figure 4 The results show that all three embodiments have excellent comprehensive mechanical properties, with tensile strength R m ≥970MPa, yield strength R p0.2 ≥870MPa, elongation A is 11-15%, and the room temperature tensile mechanical properties are better than the standard of TC4 in GB / T 13810-2017 (R m ≥930MPa, R p0.2 ≥860MPa, A≥10%), which can meet the requirements of clinical medical implant materials. Under room temperature tensile conditions, the solid solution-aged Ti-13Nb-13Zr medical alloy is not only non-toxic and harmless, but also has excellent toughness, achieving a good match between strength and plasticity. After implantation, it can avoid the adverse effects of toxic elements on the human body, and has excellent load-bearing capacity and deformation resistance, which is conducive to long-term effective implantation.

[0070] The above description is only a preferred implementation manner of the present invention, but the protection scope of the present invention is not limited thereto, and any modification and replacement based on the technical solution and inventive concept provided by the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the strength and toughness of Ti-13Nb-13Zr medical titanium alloy manufactured by laser additive manufacturing, characterized in that The following steps are involved: (1) Spherical Ti-13Nb-13Zr titanium alloy powder with a particle size of 15~45μm is used as raw material; (2) placing the spherical Ti-13Nb-13Zr titanium alloy powder of step (1) in a vacuum drying oven, heating to 70-80°C under a vacuum degree of 10-25 Pa, and keeping the temperature for 30-60 min to obtain a dried powder; (3) The spherical Ti-13Nb-13Zr titanium alloy powder dried in step (2) is placed in a powder box of a laser additive manufacturing device, and the powder is evacuated to 8-10 Pa, and then argon gas with a purity of 99.99% is continuously introduced. Under the process conditions of laser power of 90-120 W, scanning speed of 1300-1500 mm / min, scanning spacing of 0.03-0.07 mm, and layer height of 0.02-0.05 mm, the powder spreading-melting is continuously performed according to the pre-set layer cutting data and layer cutting scanning data of the laser additive manufacturing device until a deposited Ti-13Nb-13Zr titanium alloy is obtained; (4) placing the deposited Ti-13Nb-13Zr titanium alloy obtained in step (3) into a vacuum tube furnace, evacuating to 20-25 Pa, and continuously introducing argon gas with a purity of 99.99%; heating to 640-660° C. at a rate of 3-10° C. / min, keeping the temperature for 50-80 min, then taking it out, quenching it in water and cooling it to room temperature to obtain a solid solution Ti-13Nb-13Zr titanium alloy; (5) The solid solution Ti-13Nb-13Zr titanium alloy obtained in step (4) is placed in a vacuum tube furnace, evacuated to 20-25 Pa, and then continuously introduced with argon gas with a purity of 99.99%; the temperature is raised to 510-530°C at a rate of 3-10°C / min, kept at this temperature for 5-6 hours, then taken out and air-cooled to room temperature to obtain an aged Ti-13Nb-13Zr titanium alloy.

2. The method for improving the toughness of Ti-13Nb-13Zr medical titanium alloy manufactured by laser additive manufacturing according to claim 1, characterized in that: The chemical composition of the spherical Ti-13Nb-13Zr titanium alloy powder in step (1) is as follows: Nb: 12.5~14.0wt.%, Zr: 12.5~14.0wt.%, Fe: ≤0.25wt.%, C: ≤0.08wt.%, N: ≤0.05wt.%, H: ≤0.012wt.%, O: ≤0.15wt.%, and the remainder is Ti.

3. The method for improving the toughness of Ti-13Nb-13Zr medical titanium alloy manufactured by laser additive manufacturing according to claim 1, characterized in that: The spherical Ti-13Nb-13Zr titanium alloy powder in step (1) is prepared by electrode induction melting and inert gas atomization.